Synthesis of Activated Carbon from Petung Bamboo Stems (Dendrocalamus Asper) Using Microwave-Assisted Pyrolysis (MAP) Process for Biogas Storage (Universitas Negeri Semarang, 2022)
Biogas has emerged as a promising alternative to gasoline due to the depletion of fossil energy and environmental concerns. An investigation was conducted to study the technical feasibility of an adsorbed natural gas (ANG) storage system using petung bamboo-activated carbons. The activated carbons were prepared by microwave-assisted pyrolysis (MAP) and a hybrid heating system for comparison. Microwave-assisted pyrolysis is a promising alternative technology for biochar production because it has several advantages over conventional pyrolysis such as uniform heating temperature, lower energy consumption, and uniform pore size. The characteristics of the obtained activated carbons were evaluated by scanning electron microscope (SEM) and Fourier transform infrared spectroscopy. The results showed that the higher power led to the shorter pyrolysis time. However, at a certain point, the higher power causes the biomass is not degraded completely. In this case, a microwave oven with 2 magnetrons produces a better heating temperature profile than the use of 1 magnetron. The character of activated carbon prepared using 70% power output (1120 W) is better than activated carbon prepared using 60% power output (960 W). In this condition, the pore size is more uniform and the number of functional groups is less. This implies that the petung bamboo activated carbon is the ideal candidate for ANG storage.